The effects of resistance training on endurance distance running performance among highly trained runners: a systematic review - Yamamoto, L. M.; Lopez, R. M.; Klau, J. F.; Casa, D. J.; Kraemer, W. J.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2008)
The current perception among highly competitive endurance runners is that concurrent resistance and endurance training (CT) will improve running performance despite the limited research in this area. The purpose of this review was to search the body of scientific literature for original research addressing the effects of CT on distance running performance in highly competitive endurance runners. Specific key words (including running, strength training, performance, and endurance) were used to search relevant databases through April 2007 for literature related to CT. Original research was reviewed using the Physiotherapy Evidence Database (PEDro) scale. Five studies met inclusion criteria: highly trained runners (> 30 mile/wk or > 5 d/wk), CT intervention for a period ? 6 weeks, performance distance between 3K and 42.2K, and a PEDro scale score > 5 (out of 10). Exclusion criteria were prepubertal children and elderly populations. Four of the five studies employed sport-specific, explosive resistance training, whereas one study used traditional heavy weight resistance training. Two of the five studies measured 2.9% improved performance (3K and 5K), and all five studies measured 4.6% improved running economy (RE; range = 3-8.1%). After critically reviewing the literature for the impact of CT on high-level runners, we conclude that resistance training likely has a positive effect on endurance running performance or RE. The short duration and wide range of exercises implemented are of concern, but coaches should not hesitate to implement a well-planned, periodized CT program for their endurance runners.